2019
DOI: 10.2807/1560-7917.es.2019.24.4.1800005
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing–based analysis of tuberculosis (TB) in migrants: rapid tools for cross-border surveillance and to distinguish between recent transmission in the host country and new importations

Abstract: BackgroundThe analysis of transmission of tuberculosis (TB) is challenging in areas with a large migrant population. Standard genotyping may fail to differentiate transmission within the host country from new importations, which is key from an epidemiological perspective.AimTo propose a new strategy to simplify and optimise cross-border surveillance of tuberculosis and to distinguish between recent transmission in the host country and new importationsMethodsWe selected 10 clusters, defined by 24-locus mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…We propose a shortcut based on tailoring strain-specific PCRs, targeting multiple marker SNPs for the strain to be surveyed taken from the WGS data. In previous studies, we demonstrated the efficiency and versatility of this novel approach for optimizing surveillance of actively transmitted strains 1,16 , fast-tracking secondary cases after importation of XDR-TB 17 , determining the presence and/or prevalence of an outbreak strain in a population by analyzing large collections in remarkable short periods of time [18][19][20] , and differentiating between recent transmission and importation in clusters involving migrants 4 . Additionally, this strategy has a potential clinical usefulness when tracking resistant strains, as it would allow us to assume the resistance profile of the tracked strain for a new case infected with it, without the need of characterizing specifically the resistance mutations 1,19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We propose a shortcut based on tailoring strain-specific PCRs, targeting multiple marker SNPs for the strain to be surveyed taken from the WGS data. In previous studies, we demonstrated the efficiency and versatility of this novel approach for optimizing surveillance of actively transmitted strains 1,16 , fast-tracking secondary cases after importation of XDR-TB 17 , determining the presence and/or prevalence of an outbreak strain in a population by analyzing large collections in remarkable short periods of time [18][19][20] , and differentiating between recent transmission and importation in clusters involving migrants 4 . Additionally, this strategy has a potential clinical usefulness when tracking resistant strains, as it would allow us to assume the resistance profile of the tracked strain for a new case infected with it, without the need of characterizing specifically the resistance mutations 1,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative multinational efforts provide an opportunity to offset local limitations. Joint studies revealed settings with active transmission of MDR-TB [1][2][3] and made it possible to evaluate the impact on host countries of the distribution of resistant strains introduced by migrant TB cases, which are circulating in their countries of origin 4,5 .…”
Section: Screening Of Inmates Transferred To Spain Reveals a Peruvianmentioning
confidence: 99%
See 2 more Smart Citations
“…WGS provides valuable information to assist individual patient management and public health responses, but widespread implementation in resource-limited settings remains unrealistic at present. Enhanced polymerase chain reaction (PCR) based methods may be more feasible in the interim, both for genetic drug resistance determination and transmission tracking [49]. In time, the establishment of global TB surveillance systems will complement epidemiological surveillance and could track cross-border transmission dynamics, but also pose risks to personal freedom that should be considered (see Ethics section).…”
Section: Tb Surveillance and Monitoringmentioning
confidence: 99%